KEBERKESANAN PERISIAN MULTIMEDIA INTERAKTIF KOKURIKULUM MELALUI TEORI KECERDASAN PELBAGAI DALAM AKTIVITI UNIT BERUNIFORM - Abdul Karim, Mohd Sharin; Esa, Prof. Madya Dr Hj Ahmad; Mohamad Suhaimy, Prof. Madya Dr Khairul Azman (Journal of Techno-Social, 2013)
Co-curricular is the educational activities and experiences done outside normal classroom which is the continuation and reinforcement to the learning activities in the classroom contributing to the improvement of students’ academic achievement. The ‘ties and knots’ skill is a compulsory skill in the uniform unit’s syllabus. The teachers need to teach and assess each of these skills in order for each uniform unit’s member to achieve the required achievement level, and using hands on technique is no longer relevant in dealing with this transformation issue. Therefore, to address this issue, an Interactive Co-curricular Multimedia Software for uniform unit was developed for the ‘ties and knots’ topic using the teaching design model that considers students opinions and the multiple intelligences theory through various software construction design using ADDIE model. Using this approach, the teachers use hands on techniques with the help of the software and make this interactive material as reference, guideline and exercise for reinforcement and assessment based on testing technique that suits the current trend in acknowledging students achievement. This approach is hoped to solve teachers’ dilemma in guiding and assessing the students to master the ‘ties and knots’ skill and as a guideline for the students to completely master the skill easily, clearly and interactively in order to attract their interest and influence their tendency to the maximum in the uniform unit activities.